Experience of anti-adhesion barrier in the complex therapy of patients with uterine factor infertility - N.I. Nasyrova; Yu.E. Dobrokhotova; L.A. Ozolinya; M.Z. Argun; K.V. Mirskaya (LCC «Medicine-Inform», 2023)
N.I. Nasyrova1,2, Yu.E. Dobrokhotova2, L.A. Ozolinya2, M.Z. Argun1, K.V. Mirskaya1 1Central Clinical Hospital of Civil Aviation, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to determine the efficacy of hyaluronic acid anti-adhesion barrier in the complex therapy of uterine factor infertility. Patients and Methods: the retrospective study included data from 95 female patients aged 23 to 39 years with various forms of intrauterine pathology. Female patients were divided into 2 groups: group 1 (n=36) - intraoperative injection of hyaluronic acid anti-adhesion barrier into the uterine cavity, group 2 (n=59) - no injection of gel. All patients underwent surgical treatment according to the generally accepted recommendations. Transvaginal ultrasound, analyzing the endometrial thickness and structure, was performed 3 months after the surgery. After conducting the corresponding complex treatment, the pregnancy frequency was evaluated for 24 months. Results: in the post-surgical period in group 1, there was a normal echographic endometrial image observed in 30 (83.3%) female patients, and in 6 (16.7%) there were indirect signs of chronic endometritis. In group 2, only 16 (27.1%) female patients had a normal echographic picture, while 15 (25.4%) showed signs of chronic endometritis, and 14 (23.7%) had the intrauterine adhesions, indicated a high probability of intrauterine synechiae recurrence without the use of an anti-adhesion barrier. The total number of female patients who implemented reproductive life planning was 28 (77.8%) in group 1 and 31 (52.5%) in group 2 (p<0.05). Conclusion: it was shown that there was a high risk of intrauterine synechiae after intrauterine interventions with subsequent disorder of reproductive function. The use of hyaluronic acid anti-adhesion barrier during intrauterine surgical interventions can be considered as prevention of intrauterine post-surgical adhesions. The administration of hyaluronic acid anti-adhesion barrier into the uterine cavity significantly improved the reproductive prognosis in female patients with uterine factor infertility. Keywords: infertility, uterine factor infertility, intrauterine synechiae, anti-adhesion barrier, hyaluronic acid. For citation: Nasyrova N.I., Dobrokhotova Yu.E., Ozolinya L.A., Argun M.Z., Mirskaya K.V. Experience of anti-adhesion barrier in the complex therapy of patients with uterine factor infertility. Russian Journal of Woman and Child Health. 2023;6(4):326-331 (in Russ.). DOI: 10.32364/2618-8430-2023-6-4-1.